Peran Teknologi Dalam Perkembangan E-Business - Afdolli Iman Ritonga; Rizki Hambali Hasibuan; Raihan Adha Rahman Pohan; Khoirun Nisa Lubis; Nurbaiti Sirait (VISA: Journal of Vision and Ideas, 2023)
The introduction of technology in business is just one example of how the trading system in Indonesia has advanced over the years. The availability of electronic commerce has the potential to speed things up, save money and make buying and selling of goods, services, clothing, food, and other goods much quicker. The purpose of this research is to investigate how information technology contributes to the growth of e-business. This qualitative research uses data from a literature review. Especially with the internet, the rapid development of information technology has emerged as the main means of obtaining information quickly and simply. The Internet is a global computer network that connects the whole world together. People can get all the information they need from the internet. The internet can also be used to search for data or information, making it easier for the general public to get the information and communication they need. This research shows that the application of a technology-based information system within a company can provide benefits for the company such as supporting operational and managerial activities and being able to provide data that has good analytical skills in calculating data. Keywords : e-business, technology, web